The Impact of Corporate Governance on the Disclosure of Sustainability Report - Citra Adi Oktania Kumaladewi; Anna Sumaryati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The study aims to investigate how corporate governance impacts sustainability report disclosure in mining companies that are listed between 2021 and 2024 on the Indonesia Stock Exchange (IDX). The proportion of independent board members, the number of audit committee meetings held, and the level of managerial ownership are used to evaluate corporate governance. Using secondary data from the companies' official websites, a quantitative research approach is used. Purposive sampling was applied to select the sample from an initial population of 198 firms, based on two criteria: (1) being in the mining industry and listed on the IDX during the designated timeframe, and (2) regularly publishing sustainability and annual reports. By applying these criteria, a sample of 47 businesses was obtained, producing 188 observations in total. Multiple linear regression was used to analyze the data using SPSS version 25. The results of the partial test show that while the percentage of independent board commissioners has no discernible effect on sustainability report disclosure, the frequency of audit committee meetings and managerial ownership have a significant and positive impact. These findings demonstrate how important internal ownership and an active audit function are to raising the standard of sustainability accountability and transparency.